2003
DOI: 10.1074/jbc.m301975200
|View full text |Cite
|
Sign up to set email alerts
|

Antimonial-induced Increase in Intracellular Ca2+ through Non-selective Cation Channels in the Host and the Parasite Is Responsible for Apoptosis of Intracellular Leishmania donovani Amastigotes

Abstract: The capability of the obligate intracellular parasites like Leishmania donovani to survive within the host cell parasitophorous vacuoles as nonmotile amastigotes determines disease pathogenesis, but the mechanism of elimination of the parasites from these vacuoles are not well understood. By using the anti-leishmanial drug potassium antimony tartrate, we demonstrate that, upon drug exposure, intracellular L. donovani amastigotes undergo apoptotic death characterized by nuclear DNA fragmentation and externaliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
126
0
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(139 citation statements)
references
References 50 publications
4
126
0
6
Order By: Relevance
“…6C). These alterations in redox potential are consistent with recent reports (34,35) that cells enter an apoptotic-like state in response to Sb III . The generation of excessive reactive oxygen species is seen as an important factor in apoptosis.…”
Section: T[sh] 2 Coupled With Inhibition Of Gsh and T[sh] 2 Biosynthesupporting
confidence: 92%
See 2 more Smart Citations
“…6C). These alterations in redox potential are consistent with recent reports (34,35) that cells enter an apoptotic-like state in response to Sb III . The generation of excessive reactive oxygen species is seen as an important factor in apoptosis.…”
Section: T[sh] 2 Coupled With Inhibition Of Gsh and T[sh] 2 Biosynthesupporting
confidence: 92%
“…1C). Third, similar decreases in specific activities of intracellular 35 S-labeled GSH and T[SH] 2 are observed with or without Sb III throughout the incubations. Thus turnover through degradation and re-synthesis of these pools are unaffected by Sb III .…”
Section: T[sh] 2 Coupled With Inhibition Of Gsh and T[sh] 2 Biosynthesupporting
confidence: 53%
See 1 more Smart Citation
“…The pellet was discarded and the suspension was loaded on percoll gradient to isolate amastigotes from macrophages. 51 The purity was verified under phase contrast microscope.…”
Section: Purification Of Amastigotes From Infected Macrophagesmentioning
confidence: 99%
“…However, the specific targets in these pathways have not been identified. More recent studies have reported apoptosis in Sb(III)-treated amastigotes involving DNA fragmentation and externalization of phosphatidylserine on the outer surface of the plasma membrane (130,139). However, these effects do not involve the classical caspasemediated pathway (130) and do not meet the more recent stringent definition of apoptosis (85).…”
Section: Antimonialsmentioning
confidence: 99%